2011
DOI: 10.1523/jneurosci.5519-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Akt Suppresses Retrograde Degeneration of Dopaminergic Axons by Inhibition of Macroautophagy

Abstract: Axon degeneration is a hallmark of neurodegenerative diseases, including Alzheimer's disease and Parkinson's disease. Such degeneration is not a passive event but rather an active process mediated by mechanisms that are distinct from the canonical pathways of programmed cell death that mediate destruction of the cell soma. Little is known of the diverse mechanisms involved, particularly those of retrograde axon degeneration. We have previously observed in living animal models of degeneration in the nigrostriat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
113
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(115 citation statements)
references
References 61 publications
2
113
0
Order By: Relevance
“…Indeed, we have reported that both Myr-Akt and hRheb(S16H) are capable of providing such protection acutely following neurotoxin injection. 18 Alternatively, axon degeneration may ultimately have taken place over the course of the four postlesion weeks, but following this axon loss, new axon growth from remaining neurons may have been induced. Such a possibility is in keeping with our proposal that hRheb induces sprouting in normal adult dopamine neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we have reported that both Myr-Akt and hRheb(S16H) are capable of providing such protection acutely following neurotoxin injection. 18 Alternatively, axon degeneration may ultimately have taken place over the course of the four postlesion weeks, but following this axon loss, new axon growth from remaining neurons may have been induced. Such a possibility is in keeping with our proposal that hRheb induces sprouting in normal adult dopamine neurons.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16] We have demonstrated that transduction of dopamine neurons of the substantia nigra (SN) with a constitutively active form of Akt, myristoylated-Akt (Myr-Akt), induces an array of neurotrophic effects in these neurons, including hypertrophy, increased expression of neurotransmitter synthetic enzymes, axon sprouting, and resistance to neurotoxin-induced cell death 17 and axon degeneration. 18 While these observations provide a compelling proof-of-concept, that an adeno-associated virus (AAV) vector in current clinical use 19 can be used to mediate neurotrophic effects by cellular transduction, further investigation with a specific focus on the pathways that mediate clinically important phenotypic effects is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Cellular phenotypes of necrosis, apoptosis, and autophagy can indeed coexist in the same cell (Lemasters et al 2002). In addition, cell soma and axon degeneration may be governed by different pathways (Bilsland et al 2002;Raff et al 2002;Ries et al 2008;Cheng et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Even though inhibition of autophagy leads to cell death and neurodegeneration (Rubinsztein, 2006;Sarkar and Rubinsztein, 2008;Wang et al, 2009), excessive autophagy by inhibition of Rheb-mTORC1 pathway can result in axon degeneration following acute injury (Cheng et al, 2011b). Increased Akt-mTORC1 dependent macroautophagy induces retrograde axon degeneration in dopaminergic neurons after acute chemotoxic injury (Cheng et al, 2011b;Wang et al, 2012).…”
Section: Rheb In Neuroprotection and Axon Regenerationmentioning
confidence: 99%
“…Increased Akt-mTORC1 dependent macroautophagy induces retrograde axon degeneration in dopaminergic neurons after acute chemotoxic injury (Cheng et al, 2011b;Wang et al, 2012). Therefore, the ability of Akt or Rheb to protect axons from retrograde degeneration is likely to be due to its ability to suppress autophagy through mTORC1 signaling (Cheng et al, 2011b).…”
Section: Rheb In Neuroprotection and Axon Regenerationmentioning
confidence: 99%